Estudo in vitro e in vivo da osseointegração de implantes de titânio com superfícies biomimetizadas - Busquim, Thaís de Paula (2012)
The researchrs conducted with implants are seek to improve the quality of products in order to reduce the waiting time after the surgery to undergo implants on chewing loads safely. To meet this expectation it must be considered that the body has a minimum time to perform the reactions that lead to osseous integration. This study was conducted to characterize the existing titanium oxide layer in commercial implants anodized (Vulcano Actives ®) and treated with acid (Master Porous ®) and compare with a non-commercial implant with ion deposition on the surface (Porous Nano ®). The study consisted of changing the surface morphologies of titanium implants to accelerate the process of osseous integration. In vitro analyses of surfaces were performed, as well as, (roughness, chemical composition, wettability) "in vivo" (indirect measure of osseointegration). The implants were inserted in rabbit s tibia and the rabbits were sacrificed 90 days after implantation. The composition of the passive film was analyzed by x-ray photoelectron spectroscopy (XPS), RAMAM spectroscopy, electron microscopy and x-ray diffraction. The results showed that implants treated by anodizing there is predominance of anatase type of titanium oxide on the surface. The others surfaces of implants have very thin oxide and the characterization techniques available have not been able to identify the allotropic form of titanium oxide. The results of the tests showed that the higher value of roughness, the greater contact angle and removal torque of implants was reached at anodized surface implants. Surface treatments show that it is possible to reduce the time of activation of the implant with security, you can get a bone-implant interface with mechanical strength appropriate to support the oral critical forces in clinical situations, such as bone of low quality. Incubation of neutrophils in the different areas showed that in short time of interaction surface morphology is the most important feature, while at longer time chemical composition has a positive effect on cellular interaction. Spectrophotometry revealed that the adsorption of fibronectin (FN) in Porous surfaces and those Doped with Na and F is similar (80%). The association indexes of osteoblastics cells in the samples with and without FN and the values of radioactivity of samples suggest that the incorporation of FN is conclusive citocompatibility of surfaces. The surface coating of titanium with FN proved to be a great option for the treatment of dental implants to optimize and accelerate the process of osseointegration.